Patients at a drug detoxification center share perspectives on how to increase hepatitis C treatment uptake: A qualitative study. (1st March 2021) - Assoumou, Sabrina A.; Sian, Carlos R.; Gebel, Christina M.; Linas, Benjamin P.; Samet, Jeffrey H.; Bernstein, Judith A.
Highlights: Active substance use is an important barrier to HCV treatment uptake. HCV treatment should be included within an existing substance use treatment program. New models could involve high-intensity wraparound care and patient navigation. Attention to housing and respect for autonomy are also essential. Abstract: Background: The US opioid crisis is associated with a surge in hepatitis C virus (HCV) infections among persons who inject drugs (PWID), and yet the uptake of HCV curative therapy among PWID is low. Purpose: To explore potential solutions to overcome barriers to HCV treatment uptake among individuals at a drug detoxification center. Methods: Qualitative study with in-depth interviews and thematic analysis of coded data. Results: Patients (N = 24) had the following characteristics: mean age 37 years; 67 % White, 13 % Black, 8 % Latinx, 4 % Native Hawaiian/Pacific Islander, 8 % other; 71 % with a history of injecting drugs. Most patients with a positive HCV test had not pursued treatment due to few perceived immediate consequences from a positive test and possible complications arising in a distant poorly imagined future. Active substance use was a major barrier to HCV treatment uptake because of disruptions to routine activities. In addition, re-infection after treatment was perceived as inevitable. Patients had suggestions to improve HCV treatment uptake: high-intensity wraparound care characterized by frequent interactions with supportive services; same-day/walk-in options; low-barrier access to substance use treatment; assistance with navigating the health care system; attention to immediate needs, such as housing; and the opportunity to select an approach that best fits individual circumstances. Conclusions: Active substance use was a major barrier to treatment initiation. To improve uptake, affected individuals recommended that HCV treatment be integrated within substance use treatment programs. Such a model should incorporate patient education within low-barrier, high-intensity wraparound care, tailored to patients' needs and priorities.